Value Stream Mapping sebagai Upaya Pengurangan Waste di Departemen S PT A - Novitriana Anggraini Sudjianto; Liem Yenny Bendatu; I Gede Agus Widyadana (Jurnal Titra, 2013)
PT A is a manufacturer company which produces cigarette. PT A wants to do continuous improvement by keeping on reducing waste in S department. Value Stream Mapping (VSM) is a method that has been used to identify value added activity and non value added activity (waste) in that company.Based on the current value stream mapping of brand Y, there are 3 types of wastes which are inventory, transportation, and waiting. The proposed improvements will reflect in the future value stream mapping and reduce the total lead time by 5.82 %.